Crafting personalized learning paths with AI for lifelong learning: a systematic literature review - Bayly-Castaneda, K.; Ramirez-Montoya, M-S.; Morita-Alexander, A. (Frontiers in Education, 2024)
The rapid evolution of knowledge requires constantly acquiring and updating skills, making lifelong learning crucial. Despite decades of artificial intelligence, recent advances promote new solutions to personalize learning in this context. The purpose of this article is to explore the current state of research on the development of artificial intelligence-mediated solutions for the design of personalized learning paths. To achieve this, a systematic literature review (SRL) of 78 articles published between 2019 and 2024 from the Scopus and Web or Science databases was conducted, answering seven questions grouped into three themes: characteristics of the published research, context of the research, and type of solution analyzed. This study identified that: a) the greatest production of scientific research on the topic is developed in China, India and the United States, b) the focus is mainly directed towards the educational context at the higher education level with areas of opportunity for application in the work context, and c) the development of adaptive learning technologies predominates; however, there is a growing interest in the application of generative language models. This article contributes to the growing interest and literature related to personalized learning under artificial intelligence mediated solutions that will serve as a basis for academic institutions and organizations to design programs under this model.